The globular cluster system of NGC 6822 - Veljanoski, Jovan; Huxor, Avon P. (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We present a comprehensive analysis of the globular cluster (GC) system of the Local Group dwarf irregular galaxy NGC 6822. Our study is based on hom